The Interaction Between the Aggregate Behaviour of Technical Trading Systems and Stock Price Dynamics - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2007)
This study analyses the interaction between the aggregate trading behaviour of technical models and stock price fluctuations in the S&P 500 futures market. It examines 2,580 widely used trading systems based on 30-minutes prices. The sample comprises trend-following as well as contrarian models. It shows that technical trading exerts an excess demand pressure on the stock market. This is because technical models produce clusters of trading signals that are on the same side of the market, either buying or selling. Initial stock price changes triggered by news are strengthened by a sequence of trading signals produced by trend-following models. Once 90 percent of the models have signalled a particular position, stock prices tend to move in the direction congruent with the position-holding of the models. This phenomenon has to be attributed to the transactions of non-technical traders, perhaps amateurs. Once price movements lose their momentum, contrarian technical models contribute to reversals of the trend.
Keywords: 330; Technical trading; stock price dynamics; momentum effect; reversal effect; Finanzanalyse; Börsenkurs; Börse; USA